The challenges implementation of photovoltaic system in the office buildings / Muhammad Zaidi Ismail - Ismail, Muhammad Zaidi (Faculty of Architecture, Planning and Surveying, 2015)
World energy consumption based on the fossil fuel is rapidly increasing year by year. The energy based fossil fuel has many disadvantages such as non-renewable sources, high cost, produce carbon dioxide emission that hazadous to the enviroment. Therefore, this kind of energy need to be replace by an alternative energy such as solar energy. The solar energy has a huge potential in order to produce electricity in Malaysia and has many advantage such as produce clean energy, require little maintenance and no harmful emission produced. However, the solar energy is abundant if compared with another type of alternative energy. In order to develop solar energy, there are several method can be used to harvest the sunlight and produce an electricity. For this research, the author will only focus on the photovoltaic system as one method to produce the solar energy. In this research, the author will describe the definition of photovoltaic system, the components of photovoltaic system such as photovoltaic cells, inverter and others. This research also will discuss about the building integrated photovoltaic which is one of the way to integrate the photovoltaic system and the maintenance of this system. After that, the author will discuss about the factor need to be considered for photovoltaic system implementation, then followed with the development of this system in Malaysia. There are several case study has been chose to archieve the research’s objective which is the diamond building, digi building and GreenTech Malaysia GEO building. All of these three case study will be discusses about it’s photovoltaic system that has been implement in the building. The inteview session and questionnaire will be distributed and the data will be analyze. The result will be presented in graph and table as shown in the Chapter 5. The finding of this research will be determined by the mean score. There are sfeveral dimension will be make to obtain the results such as the reason photovoltaic system not fully implemented in Malaysia, the factor implement photovoltaic system, reason of development of photovoltaic system in the building is slower, the advantages of photovoltaic system, the ways to know photovoltaic system work efficiently, the ways to maintain the efficiency of the photovoltaic system, the ways to increase the development of photovoltaic system and finally the challenges to implement the photovoltaic system in the building. All the result obtained will be discussed at the Chapter 5. At the end of this research, the author will make a conclusion and recommendation regarding the challenges implementation of the photovoltaic system in the office buildings.